The Effect of Work Motivation and Burnout on Employee Performance at Perumda Tirta Mangkaluku in Palopo City - Ainun, Nur; Saharuddin, Saharuddin; Rismawati, Rismawati; Navghare, Ramakant Amar (PT. EQUATOR SINAR AKADEMIA, 2026)
The purpose of this study is to determine the effect of work motivation and burnout on employee performance at Perumda Tirta Mangkaluku in Palopo City. This study uses a quantitative method with data collection techniques through the distribution of questionnaires. This study uses the probability sampling technique, namely simple random sampling, with a total of 76 respondents, namely employees of Perumda Tirta Mangkaluku in Palopo City. The data analysis technique used in this study was multiple linear regression analysis using SPSS version 27. The results of this study indicate that Work Motivation has a positive and significant effect on Employee Performance, while Burnout has a negative and significant effect on Employee Performance. Meanwhile, Work Motivation and Burnout have a simultaneous effect on Employee Performance. This study is expected to serve as a reference for further research and for companies to consider paying more attention to employees in order to improve employee performance at Perumda Tirta Mangkaluku in Palopo City.